Resposta :
Explicação passo-a-passo:
delta = (-2)^2 - 4 2.1
delta = 4 - 4.2.1
delta = 4 - 8
delta = -4
como delta é negativo total de raízes é zero
entendeu ?
Explicação passo-a-passo:
...........................................................
![Ver imagem GGOIG](https://pt-static.z-dn.net/files/dd4/d81dcbf17c19b420b72983cd9c77d2da.jpg)
Explicação passo-a-passo:
delta = (-2)^2 - 4 2.1
delta = 4 - 4.2.1
delta = 4 - 8
delta = -4
como delta é negativo total de raízes é zero
entendeu ?
Explicação passo-a-passo:
...........................................................